Valuation of PT TBS Energi Utama Tbk Amid its Green Energy Transition - Laksono, Vari Noor (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Climate concerns are pushing global investors and governments to shift capital toward companies that demonstrate measurable ESG commitments. PT TBS Energi Utama Tbk (TOBA), formerly reliant on coal-fired power and mining, has embraced this transition through its TBS2030 roadmap. Following the divestment of its coal-fired power plants in 2024, TOBA has pivoted toward electric vehicles, renewable energy, and waste management. This transformation prompts an important valuation question: how does the transition toward Net Zero Emissions (NZE) impact TOBA’s intrinsic value? This research assesses TOBA’s value using the Discounted Cash Flow (DCF) method with a 10-year forecast under three strategic scenarios, excluding coal-fired power revenue post-2024. Segment-level modeling includes residual coal mining, Electrum (EV venture), PLTS assets, palm oil, and the newly acquired Sembcorp Environmental Management waste unit. Scenario analysis results show strong upside potential. Under the base scenario (moderate renewable growth), the implied share price is Rp1,857. Under the best-case scenario (accelerated execution in green businesses), the implied valuation reaches Rp2,854. Even in the worst-case scenario (delays in renewable scale-up), the share price is valued at Rp1,122. Compared to the current market price of Rp398 as of May 2025, the margin of safety is significant: 367% (base), 617% (best), and 182% (worst). These findings suggest TOBA is materially undervalued by the market. The research concludes that TOBA's transition strategy, if executed effectively, not only aligns with Indonesia's NZE goals but also offers substantial value creation for investors. The company is recommended to continue optimizing capital structure, expanding ESG initiatives, and leveraging green financing to unlock further value. This case demonstrates how ESG integration and business diversification can translate into financial outperformance in emerging markets.